(untitled) (Bangladesh Journal of Medical Science, 2016)
Introduction: A variety of symptoms and signs are said to be common at diagnosis of chronic myeloid leukemia, but their exact incidence is not well documented. There are conflicting opinions on the incidences of the symptoms and signs. Subjects and methodology: This is a retrospective study whereby the clinical and laboratory features of 46 patients diagnosed as chronic myeloid leukemia at different phases between 1999 and 2009 were retrieved from their case files and analyzed. Results: Of all the patients, 38, 6 and 2 presented in chronic, accelerated and blastic phases respectively. The mean age of the series was 38.3 years (range 17-68 years). The peak age of presentation was 31-40 years (30.48%) followed by 21-30 years (26.1%), 41-50 (21.7%), above 50 years (17.4%) and 10-20 years (4.3%). There was a slight male preponderance 24:22 (1.09:1) with 65% of patients being married and 35% single. Occupation wise, the ratio of petrochemical and benzene related jobs to others was 3:43 (0.07:1). Spleneomegally was the commonest presenting clinical feature in this series and was reported in 44 (95.6%) of our patients. Others were anemia, weight loss, fever, hepatomegally and night sweat. Conclusion: Because of unavailability and unaffordability of the sophisticated diagnostic tools like quantitative PCR in developing worlds, there is need for clinicians to be up to date with the usual and common clinical and laboratory features of chronic myeloid leukemia. Bangladesh Journal of Medical Science Vol.15(1) 2016 p.20-24